INFORMATION SEARCH PATTERNS OF DEPRESSION SUFFERERS IN FULFILLING MENTAL HEALTH INFORMATION NEEDS - Sohan, Indah Asnawati; Sukaesih, Sukaesih; Rohman, Asep Saeful (Edulib, 2023)
This study aims to find out the model of information search process are carried out by depression sufferers at Cahaya Bunda Cirebon Mother Children Hospital to obtain information, especially regarding mental health by using the information seeking behavior model by Kuhlthau known as ISP (Information Search Process). The research method used in this study is a qualitative research method with a case study approach. Data collection techniques were carried out through observation, interviews, and literature studies. The results of the study show that the construction that depression sufferers go through from the stage of uncertainty to understanding and in this search for information there are 6 (six) stages, namely (1) The initial stage, aware of the need for information so that the search for information is motivated by motivation in searching for information; (2) Topic Selection Stage; (3) Information Search Stage; (4) Crosscheck and validation stages to expert individuals including psychologists/psychiatrists; (5) Collection Stage, collecting information that has been sorted; and (6) Final Stage, characterized by storing information for oneself and the emergence of feelings of satisfaction and relief. The conclusion from the results of this study is that it is known that the depressed sufferers studied have a model of information search process according to the characteristics of the depressed sufferers and is sufficient to help them to obtain and use mental health information.